Lockdown fatigue among the university students at Nueva Ecija during the COVID-19 pandemic - Santiago, Jomell Miranda; Santos, Angelo Reyes; Morales, Sheila Rose Flores; Savellano, Joy Nacino (Intelektual Pustaka Media Utama, 2023)
One of the control measures to stop the transmission of COVID-19 was the implementation of a lockdown. However, after a few months of lockdown, previous research has found significant evidence of lockdown-related fatigue. Hence, the current study aimed to determine the lockdown fatigue of the students. A descriptive research design and total sampling were used. A questionnaire was developed to collect data about the sex and monthly income of the respondents and their level of lockdown fatigue and feelings after the lockdown. Permission to conduct and informed consent were obtained. Data were analyzed using various statistical tools. A total of 629 respondents participated in the study. Many of them were female and had a monthly income less than P11,690. Most of them had a moderate to high level of lockdown fatigue, and the difference in their profile was insignificant. After the lockdown period, they sometimes felt powerless, stressed, and angry, their problems were getting worse, and something unexpected would happen. Last, their feelings and lockdown fatigue level, after lockdown, had a significant positive relationship. Further studies regarding the efficacy and effectiveness of lockdowns, as well as any restriction that may jeopardize students’ health should be continually assessed by government authorities.